Climate Change and its Impact on Tourism Based Livelihood in High Mountain of Nepal - Devkota, Thakur (Journal of Development and Administrative Studies, 2017)
The climate change is the major issue of the development planning in recent world. This paper focuses on the people’s understanding and experience about the climate change, its impact on tourism dependent livelihoods of the mountain community. Participatory survey design, interview, community consultation, FGD, were conducted in the field. The literature review and hydrological and meteorological data from secondary source were collected for analysis. The people of research area feel that the fluctuation of climatic variables and extremes is occurring now and they are familiar with that change in climatic variables and associated disaster. Their experience on the warming and precipitation coincides with authorized meteorological data which depicts that the mean annual temperature is increasing and average annual precipitation is decreasing. People from High mountain region said that the impact of climate change in tourism based livelihood was experienced. All types of livelihood assets are affected by climate change in mountain region. The change in frequency and intensity of climatic variables and climate change induced hazards was observed and that retard in tourism business and tourism activities in local area.